Determination of the electron temperature and density in the negative glow of a nitrogen pulsed discharge using optical emission spectroscopy - Isola, Lucio Manuel (2010)
A new method for experimentally determining the electron density (ne) and the electron temperature (Te) in the negative glow of a nitrogen pulsed discharge is presented. It is based on optical emission spectroscopy (OES) and consists of a variation and refinement of relatively similar schemes previously reported for different working conditions by other authors. The bottom line is the measurement of the emission intensities of the (0,0) bands of the first negative system at 391.44 nm and of the (0,2) bands of the second positive system at 380.49 nm. The suggested procedure allows the establishment of the absolute values of ne and Te, as long as one calibration point is provided, such as the electron density at one specific discharge condition. If this calibration point is unavailable, the method nonetheless yields a qualitative dependence of Te and ne. Langmuir probe measurements confirm and validate the OES results for ne, thereby legitimizing the diagnostic technique developed. The interpretation of the results for Te is slightly more complex, and in some circumstances an accurate determination of Te may require further analysis.